Promoting and Maintaining Skin Integrity in End-of-Life Care: A Systematic Review. (4th November 2022) - Raepsaet, Charlotte; Blomberg, Karin; Falk-Brynhildsen, Karin; Gethin, Georgina; Beeckman, Dimitri
ABSTRACT: OBJECTIVE: To systematically review recommendations for promoting and maintaining skin integrity in end-of-life care and their level of evidence. DATA SOURCES: MEDLINE (PubMed interface), CINAHL (Cumulative Index to Nursing and Allied Health Literature), EMBASE, and The Cochrane Library were systematically searched using a combination of key terms including end-of-life care, skin care, skin hygiene, and skin cleansing . STUDY SELECTION: Articles were included if they (1) described skin care recommendations, including but not limited to the use of skin care products and interventions such as cleansing procedures; and (2) included adult patients who were expected to die within 12 months. There were no restrictions on study design, study setting, or language. Articles with a publication date before 2000 were excluded. DATA EXTRACTION: Two data extraction forms were developed. The first included information about the author, publication year, type of evidence, study topic, sample, sample size, setting, limitations of the study, level of evidence, and quality of the study. The second included recommendations for promoting and maintaining skin integrity in patients at the end of life. DATA SYNTHESIS: Because of methodological heterogeneity, results were synthesized narratively, and no meta-analysis was performed. CONCLUSIONS: The information contained in the recommendations will assist nurses in promoting and maintaining skin integrity in patients at the end of life. More research is needed on end-of-life skin care, with an emphasis on patient-centered, holistic strategies that improve patient well-being and quality of life. In most current research, recommendations are limited to literature reviews and level V evidence. Skin care must balance the promotion and maintenance of skin integrity, wound prevention, and management while promoting patient dignity and quality of life.